Interlinkages between public expenditures, non-tax government revenues and corruption in the transition economies - Alper Ozun; Hasan Murat Ertuğrul; Ergul Haliscelik (Journal of Capital Markets Studies (JCMS), 2024)
Purpose - This article examines potential impacts of increase in non-tax government revenues and public expenses on corruption for 11 transition economies in the Central and Eastern Europe. Design/methodology/approach - The empirical analysis uses yearly panel datasets and employs second-generation panel data models which take cross-sectional dependency and slope heterogeneity into account. Findings - The empirical results reveal the fact that there is a strong linkage between public expenses and corruption and a weak linkage between non-tax revenue collection and corruption in the transition economies. We perform the same analysis by using data sets from G-7 countries but do not notice any linkages between those variables. Research limitations/implications - The research topic requires further discussion on constitutional political economy to digest the empirical findings. Thus, an extended version combined with political economic approach might be useful. Practical implications - Through economic transitions, there might be a linkage between public expenditures and corruption index. Thus, public spending might be controlled by using constitutional economics policies. Originality/value - This paper is the first empirical work in the literature, which examines if there is a linkage between corruption and public expenditures and government tax income structure by using panel data sets. Moreover, it compares the results from transition countries with those of G-7 countries and provides certain policy suggestions in the context of constitutional economics.
Keywords: C33; D73; H20; 330; Constitutional economics; Corruption; Dynamic CCEMG model; Tax revenue; Transition economies